2016
DOI: 10.3855/jidc.6354
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella serovars along two beef chains in Ethiopia

Abstract: Introduction: Salmonella has been reported from foods and the food production environment, with outbreaks occurring in the human population worldwide. Methodology: A survey on Salmonella in two beef production lines (a beef abattoir line and a processing line) in Addis Ababa, Ethiopia was conducted, with a total of 668 various samples randomly collected from animal-related materials, the environment, and a beef product (mortadella). Results: Overall, a 12.9% prevalence (26.3% from the abattoir line, 5.3% from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
(46 reference statements)
1
10
2
Order By: Relevance
“…The proportion of Salmonella isolates, in the current study, recovered from swabs of carcasses of abattoir origin was 14.29%. This finding corroborates with the findings of Takele et al 6 and Dabassa and Bacha 30 who reported 11.3% and 13.3% from beef carcasses in Jimma municipal abattoir, respectively, and Hiko et al 24 who reported 11.8% from Addis Ababa Abattoirs Enterprise whereas this prevalence is lower than other reports from Tigray region (16.4%), 31 Dire Dawa abattoir (17.7%), 32 and Senegal (42.8%). 33 Counter to this, the current finding is higher than the report of El-Gamal and EL-Bahi, 34 Renatus et al, 35 Thongsay et al, 36 Kalambhe et al, 37 Bahnass et al, 38 Sefinew and Bayleyegn, 39 and Gizachew and Mulugeta 40 from Egypt (0.0%), Namibia (0.50%), Thailand (4.5%), Central India (6%), Saudi Arabia (8.5%), and Bahir Dar (4.8, 7.6%), respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The proportion of Salmonella isolates, in the current study, recovered from swabs of carcasses of abattoir origin was 14.29%. This finding corroborates with the findings of Takele et al 6 and Dabassa and Bacha 30 who reported 11.3% and 13.3% from beef carcasses in Jimma municipal abattoir, respectively, and Hiko et al 24 who reported 11.8% from Addis Ababa Abattoirs Enterprise whereas this prevalence is lower than other reports from Tigray region (16.4%), 31 Dire Dawa abattoir (17.7%), 32 and Senegal (42.8%). 33 Counter to this, the current finding is higher than the report of El-Gamal and EL-Bahi, 34 Renatus et al, 35 Thongsay et al, 36 Kalambhe et al, 37 Bahnass et al, 38 Sefinew and Bayleyegn, 39 and Gizachew and Mulugeta 40 from Egypt (0.0%), Namibia (0.50%), Thailand (4.5%), Central India (6%), Saudi Arabia (8.5%), and Bahir Dar (4.8, 7.6%), respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The current finding is higher than the report of Shilangale et al, 21 who reported a 0.85% incidence of Salmonella from the three beef export abattoirs in Namibia and the 1.5% isolation rate reported by Ibrahim 22 from cattle carcasses at Kano abattoir in Nigeria. Contrarily, this finding is lower than the reports of Wassie et al, 23 Hiko et al, 24 and Amenu 25 from Gonder (20.8%), Addis Ababa (26.6%), and Arbaminch (31.5%) municipal abattoirs, respectively.…”
Section: Discussioncontrasting
confidence: 54%
“…Salmonella Saintpaul was previously reported from camel (Molla, Salah, Alemayehu, & Mohammed, ) and minced beef (Zewdu & Cornelius, ) in the country. Another recent study also showed that S. Saintpaul was the dominant serovar in beef abattoir and beef processing plant in Addis Ababa(Hiko, Irsigler, Ameni, Zessin, & Fries, ).…”
Section: Discussionmentioning
confidence: 92%
“…Salmonella Saintpaul was previously reported from camel (Molla, Salah, Alemayehu, & Mohammed, 2004) and minced beef (Zewdu & Cornelius, 2009) in the country. Another recent study also showed that S. Saintpaul was the dominant serovar in beef abattoir and beef processing plant in Addis Ababa (Hiko, Irsigler, Ameni, Zessin, & Fries, 2016 Salmonella carried by cockroaches in a neonatal intensive care unit (Tilahun et al, 2012), and another study also showed high mortality from blood stream infection in TASH due to MDR enterobacteriaceae (Seboxa et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…In Ethiopia, different Salmonella serovars were isolated from animals and humans (Alemayehu et al, 2003;Tibaijuka et al;Ejeta et al, 2004;Aragaw et al, 2007;Zewdu and Cornelius, 2009;Sibhat et al, 2011;Beyene et al, 2011;Hiko et al, 2016;Kiflu et al, 2017;Hiko et al, 2018). However, PFGE analysis of the isolates was not conducted; thus establishing genetic relationships for epidemiological purposes is impossible.…”
Section: Introductionmentioning
confidence: 99%